2015
DOI: 10.1080/10286020.2015.1054815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of thiophosphate tricyclic coumarin derivatives as steroid sulfatase inhibitors

Abstract: Steroid sulfatase (STS) enzyme inhibition is an important approach to the management of hormone-dependent breast cancer. In this paper, we report convenient methods for the synthesis and biological evaluation of thiophosphate tricyclic coumarin analogs exhibiting STS activity. The described methods are based on the straightforward preparation of 7-hydroxy-2,3-dihydro-1H-cyclopenta[c]chromen-2-one, 3-hydroxy-7,8,9,10-tetrahydro-6H-benzo[c]chromen-6-one, and 3-hydroxy-8,9,10,11-tetrahydro-7H-cyclohepta[c]chromen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Although the mechanism of inhibition is unknown, docking studies suggest the possibility of a phosphate group transfer to fGly75 during the inactivation process. Further development led to the synthesis of thiophosphate analogues with slightly improved inhibitory potencies 79 . The highest activity (in an assay with an isolated enzyme) was exhibited by compound 34 (Table 3), which contained a chlorothiophosphate group (IC 50 value of 13.3 mM).…”
Section: Nonsteroidal Sts Inhibitors Containing Phosphorus Moietiesmentioning
confidence: 99%
“…Although the mechanism of inhibition is unknown, docking studies suggest the possibility of a phosphate group transfer to fGly75 during the inactivation process. Further development led to the synthesis of thiophosphate analogues with slightly improved inhibitory potencies 79 . The highest activity (in an assay with an isolated enzyme) was exhibited by compound 34 (Table 3), which contained a chlorothiophosphate group (IC 50 value of 13.3 mM).…”
Section: Nonsteroidal Sts Inhibitors Containing Phosphorus Moietiesmentioning
confidence: 99%
“…42 The initial strategy employed for generating a lead STS inhibitor involved replacement of the sulfate group (OSO 3 ) on the natural enzyme substrate with surrogates or mimics such as phosphates or thiophosphates. Recently, Demkowicz et al synthesized new phosphate and thiophosphate esters of tricyclic coumarin 39, 43,44 N-alkanoyl tyramine 40, 45 49 The clinical trial ndings revealed that the drug can selectively inhibit cell proliferation and induce tumor cell apoptosis through the farnesoid X receptor. In vitro assay results showed that 63 and 91% of ovarian cancers were sensitive to apomine at concentrations of 10 and 20 mM, respectively.…”
Section: Organophosphorus Compounds As Anticancer Drugsmentioning
confidence: 99%
“…Irosustat demonstrated a very potent STS inhibitory effect (IC 50 value of 8 nM) with no in vivo and in vitro estrogenic properties. Irosustat resulted to be orally active and, as such, reached clinical trials, showing great therapeutic potential in several clinical studies. To date, other coumarin derivatives with sulfamate, phosphate, , and thiophosphate moieties as well as fluorinated compounds , have been reported as potent STS inhibitors.…”
Section: Introductionmentioning
confidence: 99%